Strategi Pelayanan kepada Homo Digitalis - Hasanema Wau (TEMISIEN: Jurnal Teologi, Misi, dan Entrepreneurship, 2023)
The digital revolution has shaken the civilization. In a relatively short time there have been drastic changes in the world order. Human lifestyles are now changing in response to the relentless insistence of digital innovation. The shift that occurs at a further stage is the human understanding of the reality of the world and oneself. As far as can be admitted, even the understanding of God can be evaluated. People (individuals and groups) who vulgarly express their belief in the absence of God, are not just assumptions, but they are real! Digital technology continues to innovate and is unstoppable. Those who are not skilled to fight in the digital world have the potential to be isolated from the rapid flow of information. Technological advances are able to create a world with a new culture, from the charming, the ridiculous, the disturbing to the gripping kind of culture.It is impossible for the church to close itself to the swift currents of this change. Adapting as far as what can be tolerated is a wise move. Various domino effects on the spread of the digital era must be responded to quickly and accurately. Openness must go hand in hand with critical thinking. Digital literacy efforts must be balanced with fostering congregational members to prioritize ethics and safety in social media.Â Keywords: digital, openness, literacy, coaching